Circular Economy Approach in Organic Waste Processing as an Effort to Implementation of Green Accounting - Theresa Delania Assan; Patricia Penaten Ola Ryantobi; Matilda Florence Dura; Maria Gaudensia Uba Beda; Jesika Kristiani Rumbu Emu (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2025)
Application of circular economy and green accounting in organic waste management in Tegalalang Village, Gianyar, Bali. With the increasing amount of waste due to population growth and tourism, this village faces significant challenges in waste management, especially organic waste. The application of circular economy principles through the separation, processing, and utilization of organic waste into compost and biogas has succeeded in reducing the volume of waste and creating new economic value. In addition, green accounting is integrated to measure environmental impacts, record costs, and benefits, and increase transparency in resource management. The results of the study show that the combination of circular economy and green accounting not only increases public awareness of sustainability but also strengthens the competitiveness of local products and supports sustainable agriculture. Thus, Tegalalang Village becomes a model for the implementation of sustainable waste management practices in Indonesia.